Marburg Virus Disease: Epidemiology, Transmission, and Global Health Implications - Akram, Muhammad; Mahmood, Abid; Umaru, Isaac John; Hasan, Mohammed Khudhair; Abdulghafoor, Hind A.; Khan, Fahad Said; Ozdemir, Fethi Ahmet; Sołowski, Gaweł; Ali, Jaouher Ben; Al-Musawi, Jehan Mohammad (African Journal of Medicine, Surgery and Public Health Research, 2025)
Marburg virus disease (MVD), a severe viral hemorrhagic fever, was first identified in 1967 following simultaneous outbreaks in Marburg and Frankfurt, Germany, and Belgrade, Serbia. The initial cases were linked to laboratory exposure to African green monkeys (Chlorocebus aethiops) imported from Uganda for scientific research. Since then, sporadic cases and outbreaks have been reported across sub-Saharan Africa, particularly in Angola, Uganda, the Democratic Republic of the Congo, and, more recently, in West African countries such as Ghana. Human-to-human transmission occurs through direct contact with the blood, secretions, organs, or other bodily fluids of infected individuals, as well as via contaminated materials like bedding and medical equipment. The incubation period ranges from 2 to 21 days, after which patients typically present with hemorrhagic manifestations, shock, and multiorgan failure. Currently, there is no approved antiviral treatment, and management is limited to supportive care, including fluid resuscitation, electrolyte balance, oxygen therapy, and treatment of secondary infections. Early diagnosis, case isolation, contact tracing, and stringent infection control measures are essential to containing outbreaks. Due to its high case-fatality rate, potential for epidemic spread, and lack of licensed therapeutics or vaccines, MVD is designated a priority pathogen by the World Health Organization (WHO). In the context of increasing global attention to emerging and re-emerging infectious diseases, this review emphasizes the urgent need for investment in health system strengthening, improved diagnostic infrastructure, and the acceleration of vaccine and therapeutic development to mitigate future outbreaks.